Analysis of the fatty acid composition of Caulerpa lentillifera using Gas Chromatography Mass Spectrometry - Ab. Halim, Noorhazayti; Zamimi, Nurul Najwa; Sayed Kamar, Syarifah Haizan; Muhammad Ali, Suhaila (2019)
Caulerpa lentillifera, also known as Sea Grape or Green Caviar is a type of green seaweed from the class of Caurlepacea and species of Lentillifera. They are common seaweed communities in tropical and subtropical waters. They have different biochemical compounds from various seaweedspecies. However, the study onphytochemical components andthe biological activity of C. lentillifera are not fully understood yet. This study was carried out to determine the best extraction solvents and to evaluate the phytocomponent in the n- hexane, Dichloromethane (DCM) and methanol extract of C. lentillifera using Gas Chromatography-Mass Spectrometry (GC-MS) analysis. C. lentillifera was collected from the coastal area of Sabah, Malaysia. Then, it was subjected for purification, drying and soxhlet extraction process using n- hexane, DCM and methanol. Only fatty acid compound was analysed using a Perkin Elmer Turbo Mass Spectrophotometer. It showed that, methanol is the most efficient solvent as it recorded the highest extraction yield in C. lentillifera. Twenty phytocomponents have been identified from all extracts of C. lentillifera by GC-MS analysis. This analysis discovered the presence of major constituents like palmitic acid, oleic acid, pentadecanoic acid, behenic acid, myristic acid, etc. Many studies have shown that, most of the identified major compounds were proven to exhibit antibacterial, antifungal, anti- inflammatory, antiviral, etc. Thus, it is apparent that C. lentillifera has the potential to be used as seaweed of phytopharmaceutical importance as it contains numerous bioactive compounds.